Case Report: Cumulative proton dose reconstruction using CBCT-based synthetic CT for interfraction metallic port variability in breast tissue expanders - Chen, Chin-Cheng; Liu, Jiayi; Park, Peter; Shim, Andy; Huang, Sheng; Wong, Sarah; Tsai, Pingfang; Lin, Haibo; Choi, J. Isabelle (Frontiers in Oncology, 2023)
Dose perturbation of spot-scanning proton beams passing through a dislocated metallic port (MP) of a breast tissue expander may degrade target dose coverage or deliver excess dose to ipsilateral lung and heart. The feasibility of utilizing daily cone-beam CT-based (CBCT-based) synthetic CTs (synCTs) for dose reconstruction was evaluated, and the fractional and cumulative dosimetric impact due to daily MP dislocation is reported. The synCT was generated by deforming the simulation CT to daily CBCT. The MP structure template was mapped onto all CTs based on daily MP position. Proton treatment plans were generated with two and three fields on the planned CT (pCT, Plan A) and the first verification CT (vCT, Plan B), respectively, for a fractional dose of 1.8 Gy(RBE). Plan A and Plan B were used alternatively determined by the daily MP position. The reconstructed fractional doses were calculated with corresponding plans and synCTs, and the cumulative doses were summed with the rigid or deformed fractional doses on pCT and vCT. The planned and reconstructed fractional dose demonstrated a low-dose socket around the planned MP position due to the use of field-specific targets (FSTs). Dose hot spots with >120% of the prescription due to MP dislocation were found behind the planned MP position on most reconstructed fractional doses. The reconstructed cumulative dose shows 2 low-dose sockets around the 2 planned MP positions reflecting the 2 plans used. The doses at the hot spots behind the planned MPs averaged out to 114% of the prescription. The cumulative D95% of the CTV_Chest Wall decreased by up to 2.4% and 4.0% and the cumulative V20Gy(RBE) of the left lung decreased to 16.1% and 16.8% on pCT and vCT, respectively. The cumulative Dmean of the heart decreased to as low as 0.7 Gy(RBE) on pCT but increased to as high as 1.6 Gy(RBE) on vCT. The robustness of proton plans using FSTs around the magnet in the MP of the tissue expander can be improved by applying multiple fields and plans, which provides forgiveness of dose heterogeneity incurred from dislocation of high-Z materials in this single case.